Comparative Efficacy of Nebulized 7% Hypertonic Saline versus 3% Hypertonic Saline in Children with Acute Bronchiolitis (Journal of Dhaka Medical College, 2018)
Background: Acute bronchiolitis is an acute viral lower respiratory tract infection in early childhood and is the leading cause of hospitalization in infants below 2 years of age. Being a viral disease, there is no effective treatment of this problem other than supportive care. To provide this care, both 3% hypertonic saline and 7% hypertonic saline has been used and found effective. However, which option is more effective to reduce clinical severity and length of hospital stay, still remain unsettled.Objective: To determined the efficacy of 7% hypertonic saline in children with acute bronchiolitis.Methodology: The study was a randomized controlled trial and carried out in the Department of Paediatrics, Dhaka Medical College Hospital (DMCH), Dhaka between January 2015 to December 2016. A total of 135 children from 1 month to 2 years of age irrespective of sex with clinical presentation of acute bronchiolitis admitted in the paediatrics ward of DMCH were included in the study and were randomly assigned to either 7% nebulized hypertonic saline (Group-I = 45) or to 3% nebulized hypertonic saline (Group-II = 90) in ratio (1:2). The main outcome variables were clinical severity score and length of hospital stay. The outcome was evaluated at 12 hourly and 24 hourly intervals till discharge (up to 120 hours)Result: In this study both groups were almost similar with respect to their demographic characteristics like age and sex and baseline clinical characteristics. The study demonstrated that respiratory rate score, wheezing score, retraction score, general condition score and clinical severity score of both treatment modalities were reduced. Children of group-I(7% HS) 40(88.9%) recovered at the end of 72 hours where as 67(74.4%) of the children of group-II(3% HS) recovered from the disease during the same period. Length of hospital stay was shorter in 7% hypertonic saline group compared to 3% hypertonic saline group (56.36±16.33 hours vs63.07±21.48 hours, p=.067). The patients of 7% hypertonic saline group required a shorter duration of oxygen therapy compared to 3% hypertonic saline group (16.53±3.98) hours vs (20.25± 4.15) hours, (p=0.109) respectively.Conclusion: Nebulized 7% hypertonic saline as well as 3% hypertonic saline both were effective in acute bronchiolitis and found no significant difference in efficacy between these options in terms of reducing clinical severity, length of hospital stay and duration of oxygen therapy. No side effect were observed in either group.J Dhaka Medical College, Vol. 26, No.2, October, 2017, Page 153-156